2018
DOI: 10.1016/j.kjms.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor preserves intestinal mucosal barrier function and alters gut microbiota in mice

Abstract: The intestinal mucosal barrier (IMB) enables the intestine to provide adequate containment of luminal microorganisms and molecules while preserving the ability to absorb nutrients. In this study, we explored the effect of brain-derived neurotrophic factor (BDNF) on IMB function and gut microbiota in mice. BDNF gene knock-out mice (the BDNF group) and wild-type mice (the BDNF group) were selected. The gut microbiota of these mice was analyzed by denaturing gradient gel electrophoresis (DGGE) assay. The ultrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…These proteins play pivotal roles in maintaining the integrity of tight junction between cells and the normal function of epithelial cell barriers. Abnormal expression of these protein cause barrier dysfunction, leading to dysfunction of tight junction and increased tissue permeability, which is one of the characteristics of inflammatory bowel disease (Walsh-Reitz et al, 2005; Förster, 2008; Mir et al, 2016; Li et al, 2018; Lucke et al, 2018). In the present study, the results of immunofluorescence analysis, Real-time quantitative PCR detection and western blot analysis demonstrated that Mdc could improve diseased intestinal tight junction by up-regulating the level of tight junction proteins ZO-1, Occludin and Claudin-1.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins play pivotal roles in maintaining the integrity of tight junction between cells and the normal function of epithelial cell barriers. Abnormal expression of these protein cause barrier dysfunction, leading to dysfunction of tight junction and increased tissue permeability, which is one of the characteristics of inflammatory bowel disease (Walsh-Reitz et al, 2005; Förster, 2008; Mir et al, 2016; Li et al, 2018; Lucke et al, 2018). In the present study, the results of immunofluorescence analysis, Real-time quantitative PCR detection and western blot analysis demonstrated that Mdc could improve diseased intestinal tight junction by up-regulating the level of tight junction proteins ZO-1, Occludin and Claudin-1.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of UC is not clearly understood, and it is generally considered to be caused by multiple factors [3]. Among these, intestinal mucosal barrier function and microflora play major roles in which UC occurs and develops [4]. The intestinal mucosal barrier is the first barrier against a hostile environment, mainly formed by the tight junctions (TJs) of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hormones released during the stress response, such as cortisol, can modulate the composition and function of the intestinal mucosal barrier to affect intestinal permeability (Maqsood and Stone, 2016). The tight junctions of epithelial cells (ECs) are the main structures of the intestinal mucosal barrier (Li et al, 2018). Tight junctions consist of two proteins: occludin and claudin, both of which are transmembrane proteins.…”
Section: Introductionmentioning
confidence: 99%